Novelties in the genus Ceroxylon (Arecaceae) from Peru, with description of a new species - Galeano, Gloria (2008)
A new species of Ceroxylon from Peru, C. peruvianum, is described and illustrated. The finding of disjunctive populations of C. quindiuense in Peru is discussed.